ENHANCEMENT OF TEACHERS' LANGUAGE SKILLS IN WRITING RESEARCH ARTICLES THROUGH THE ABCD MODEL - Armida, Armida; Sumardi, Mayang Sastra; Andriani, Reni; Pratama, Aryawira; Trimadona, Eliza; Mesalina, Juliana; Fitria, Wahyuni; Sari, Mesita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
This community service program, conducted for teachers of the PGRI Association in Sabak Timur Subdistrict, Tanjung Jabung Timur Regency, aimed to enhance their language proficiency in writing research articles, particularly in English. Using the Asset-Based Community Development (ABCD) approach, the program focused on leveraging the community's existing potential and resources to address common challenges faced by teachers, such as mastering basic grammar, selecting appropriate vocabulary, and understanding scientific writing structures. The activities included intensive training sessions, workshops, and individual consultations, covering aspects like grammar, sentence construction, vocabulary enrichment, and the development of a clear and concise academic writing style. Teachers were also guided through the structure and format of scientific articles, enabling them to produce well-organized drafts. The program's outcomes included a collection of draft articles ready for submission and improved confidence among participants in contributing to academic publications. This initiative successfully empowered teachers to elevate their research writing skills, fostering a culture of academic excellence and innovation within their community.